50-pound autoclave and casting equipment (1937)
General view of a 50-pound autoclave and polymer casting equipment used during the early stages of nylon production and research at the DuPont Experimental Station in Wilmington, Delaware. During production, a partially-evaporated nylon salt solution was fed into the autoclave and heated to 275 degrees centigrade under a pressure of 275 pounds per square inch in order to precipitate polymerization. Once polymerization occurred, additional water was bled off and the pressure was slowly reduced to atmospheric levels before the polymer was extruded. As visible on the right-hand side of the photograph, the hot polymer ribbon was extruded and wound onto a reel before being broken into nylon chips for spinning.
Keywords: Nylon; Polymers; Nylon--Testing; E.I. du Pont de Nemours & Company. Experimental Station; E.I. du Pont de Nemours & Company; Machinery; Autoclaves